A conjoint analysis of stated vaccine preferences in Shanghai, China. Issue 6 (5th February 2020) - Sun, Xiaodong; Wagner, Abram L.; Ji, Jiahui; Huang, Zhuoying; Zikmund-Fisher, Brian J.; Boulton, Matthew L.; Ren, Jia; Prosser, Lisa A.
Highlights: China's list of government-funded vaccines is relatively small but will increase. Shanghai parents preferred safer, more effective vaccines produced in China. Among entire population, cost did not significanlty contribute to preferences. More affluent individuals had a preference for more expensive vaccines. Abstract: It is not clear what kind of preferences parents in China would have for vaccines that could be added to a future immunization schedule. This study's aim was to assess Chinese parents' preferences for attributes of vaccines. We surveyed parents of young infants ≤3 months of age at immunization clinics in Shanghai, China, in 2017. We used a discrete choice experiment (DCE) to present parents with choices between two hypothetical profiles of vaccines which were described using the following attributes: cost, risk of side effect, location of vaccine manufacturer, vaccine testing, vaccine effectiveness, severity of disease, disease prevalence. A logistic regression output estimates of preference utilities. In total, 599 caregivers completed the DCE. Parents expressed lower preference for vaccines with a 30% chance of fever as an adverse event vs a 10% chance (OR: 0.53, 95% CI: 0.44, 0.64), for vaccines only 85% effective vs those 95% effective (OR: 0.55, 95% CI: 0.48, 0.62), and for imported vaccines (OR: 0.74, 95% CI: 0.60, 0.92) and those not tested in Chinese children (OR: 0.45, 95% CI: 0.37, 0.53) compared to domestic vaccines. More affluent groups preferred more expensive vaccines whereas less affluent groups did not express cost-based preferences. Promotion of vaccines in China should focus on parents' stated preferences, which include past testing done in Chinese children – which is, in fact, required of all licensed vaccines in China. Information about these trials could emphasize low risk of adverse events and high effectiveness.